Spielberg and Kahn: film editing and narrative control through creative collaboration - Papathanasiou, Konstantinos (2024)
The editor and the director form one of the most intimate collaborations in the film industry. From Close Encounters of the Third Kind (1977) to the present, Michael Kahn has edited virtually every film Steven Spielberg has directed. To date, Spielberg Studies has generated very little knowledge and understanding of how editing creates meaning in Spielberg's films, and of how Kahn and Spielberg work together to structure their narratives. Through close textual analysis, comparative study, editing theories, and calculations of the films' average shot length, this research examines how Spielberg and Kahn control the films' complex narratives through editing techniques and reveals aspects of their collaboration.